(untitled) (DAPesquisa, 2021)
This paper contextualizes and problematizes the inclusion of Dance in the school curriculum, from experiences in Laboratory Schools in different places in Brazil which have Dance as a mandatory class. Through participant observation it was possible to product data about each one of these school realities and promote discussions that indicate changes or continuities of area problems. It brings a brief history of the specific legislation about the teaching of Arts, and a reflection about the National Common Curricular Base, a document that regulates basic education in Brazil. It is possible to observe advancements in the consolidation of Dance as an autonomous area, although there are still some difficulties that are very similar in the different contexts studied, especially in what concerns the polyvalence in the teaching of Arts and its relation to the field of Physical Education.